PEMANFAATAN LAYANAN MAJALAH DAN KORAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI BALI - Karlinda Wirata, Made Indri; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT Utilization of magazine and newspaper services in the library at this time is still much in demand by library visitors to simply just read or be used as research and other needs. The purpose of this study was to determine the use of magazine and newspaper services in the Bali Archives and Library Service. This research uses descriptive methods and quantitative approaches. Hypothesis testing results show that the t value is smaller than alpha, it can be concluded that there is a significant influence between the use of magazine and newspaper services with user satisfaction in the Archives Service and the Provincial Library of Bali. Keywords : Utilization, Services, Magazines and Newspapers, Librarians